The strategy implementing IoT-based land transportation for sustainable transportation - Satyadharma, Maudhy; Putra, Adris Ade; Mokui, Hasmina Tari (Universitas Trunojoyo Madura, 2025)
The development carried out by the government requires the availability of infrastructure including transportation infrastructure. Today's transportation sector planning is greatly influenced by technological advances. In encouraging the realization of sustainable transportation, the application of the Internet of Things (IoT) is very much needed. This encourages the need for a strategy in analyzing the identification of problems in the implementation of sustainable transportation based on the Internet of Things (IoT) in Southeast Sulawesi Province. This study applies a qualitative method where informants are selected purposively, namely using the consideration that they understand the problems in the implementation of land transportation in the Southeast Sulawesi Province especially supporting sustainable transportation. Based on the results of this study, it was found that the strategies that need to be carried out by the Southeast Sulawesi Provincial Government in implementing Land Transportation in realizing sustainable transportation by utilizing the Internet of Things (IoT) include multi-sector collaboration, improving digital infrastructure, socialization and education, and strong regulations.